Introduction to linear algebra - Gillett, Philip (Boston, Massachusetts : Houghton Mifflin Company, 1975)
Linear algebra has become established in the undergraduate curriculum as the ideal place for students fresh out of calculus to tart taking mathematics seriously.
Chapter 1. Concrete vector spaces -- Chapter 2. Abstract vector spaces -- Chapter 3. Linear maps -- Chapter 4. Matrices -- Chapter 5. Multiplication of maps and matrices -- Chapter 6. Equivalence and similarity -- Chapter 7. Linear systems -- Chapter 8. Determinants -- Chapter 9. Eigenvalues.
Includes bibliographical references and index.
Keywords: ALGEBRA -- LINEAR